The progressive era of constitutional amendment - Albert, Richard (Revista de Investigações Constitucionais, 2015)
In this Essay I explore the impetus for the Seventeenth Amendment, which was in large measure driven by an effort to curb corruption in senatorial elections. I begin by exploring the difficulty of formal amendment in the United States. I explain the rules of formal amendment and I review briefly the empirical literature suggesting that the United States Constitution is one of the world’s most difficult to amend, if not the most difficult. Then, I discuss the Progressive Era, a period of time during which formal amendment seemed much easier than it is today. I review the movement and its purposes, and I situate the four Progressive Era amendments. Finally, I focus on one of these four amendments, the Seventeenth, and consider the motivations driving its adoption as well as current critiques about its effectiveness. I conclude by questioning whether repealing the Seventeenth Amendment would necessarily reinstate indirect senatorial elections as a matter of practice, whatever it would mean as a matter of formal law.